2022
DOI: 10.18632/aging.203954
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone attenuates neurological deficits and exerts a protective effect on damaged axons via the PI3K/AKT/mTOR-dependent pathway in a mouse model of intracerebral hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is a devastating event with high disability and fatality rates. However, there is a lack of effective treatments for this condition. We aimed to investigate the neuroprotective and axonal regenerative effects of progesterone after ICH. For this purpose, an ICH model was established in adult mice by injecting type VII collagenase into the striatum; the mice were then treated with progesterone (8 mg/kg). Hematoma absorption, neurological scores, and brain water content were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…In addition, in the presence of a PI3K inhibitor, activation of mTOR also reduced inflammation. This is in accordance with the study of Liu et al, who found that progesterone attenuated local inflammation in mice with intracerebral haemorrhage via activation of the PI3K/AKT/mTOR axis [22]. We also found that EX-Netrin1 reduced the release of inflammatory factors from microglia and promoted microglial M2 polarization.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, in the presence of a PI3K inhibitor, activation of mTOR also reduced inflammation. This is in accordance with the study of Liu et al, who found that progesterone attenuated local inflammation in mice with intracerebral haemorrhage via activation of the PI3K/AKT/mTOR axis [22]. We also found that EX-Netrin1 reduced the release of inflammatory factors from microglia and promoted microglial M2 polarization.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, netrin-1 can activate the phosphatidylinositol-3-kinase (PI3K)/protein kinase B (PKB or AKT)/mammalian target of the rapamycin (mTOR) pathway through unc5b [ 20 ]. This axis plays a vital role in promoting axonal growth and mitigating inflammation [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry/immunofluorescence was carried out using a PV9000 Immunohistochemistry Kit (Servicebio). The procedure involved (1) permeabilization; (2) serum blocking; (3) primary antibody incubation; (4) secondary antibody incubation; (5) DAPI counter‐staining of cell nuclei; (6) mounting; and (7) image capture 13 …”
Section: Methodsmentioning
confidence: 99%
“…The procedure involved (1) permeabilization; (2) serum blocking; (3) primary antibody incubation; (4) secondary antibody incubation; (5) DAPI counter-staining of cell nuclei; (6) mounting; and (7) image capture. 13 Real-time quantitative PCR (qPCR) and western blotting analysis Total RNA extraction, cDNA synthesis and qPCR were performed as previously described. 8 The primer sequences are listed in Table S2.…”
Section: Histology and Immunolabeling Analysismentioning
confidence: 99%
“…The presence of sources and receptors of progesterone within the CNS, as well as its modulation of inhibitory and excitatory amino acids, indicate a possible broader role for progesterone than simply as a gestational hormone [129][130][131]. The administration of progesterone demonstrated it to be neuroprotective in intracerebral hemorrhage (ICH) by inhibiting neuroinflammation, promoting axonal regeneration, and reducing cell apoptosis, myelin loss, neutrophil infiltration, microglia, and astrocyte activation in an animal model [132]. Several studies have shown that progesterone regulates some key features of neuronal function after SCI [133].…”
Section: Molecular Therapymentioning
confidence: 99%